Simultaneous Kidney and Liver Resection in Renal Cell Carcinoma Liver Metastases: A Tale of Two Cases - Indah Jamtani; Adianto Nugroho; Syamsu Hudaya; Rofi Y. Saunar; Aditomo Widarso; Taslim Poniman (National Cancer Center - Dharmais Cancer Hospital, 2020)
Introduction: Resection of renal cell carcinoma liver metastases (RCCLM) is known to provide a good survival outcome. Simultaneous RCCLM resection with the primary tumor is commonly done in cases with direct extension of locally advanced RCC to liver parenchyma. Cases of safe simultaneous resection of liver and kidney in malignancy have not been reported before in Indonesia. Case Presentation: We aim to describe two cases of left-sided RCC with right-sided RCCLM who underwent simultaneous kidney and liver resection. Both patients had good short-term survival with no intra-operative and post-operative complications.Conclusion: Although simultaneous kidney and liver resection poses challenges of substantial morbidity, a safe surgical and multidisciplinary approach could be implemented in selected cases with a good surgical outcome.